Situation Report: Yugoslavia, 21 January 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Yugoslav Army Adopts Wait-and-See Attitude / by Slobodan Stankovic Branko Mikulic: "A New Tito"? / by Slobodan Stankovic Tito's Widow in Fighting Spirit / by Slobodan Stankovic Campaign against Tito's Widow Escalates / by Slobodan Stankovic Cracow [Kraków] Invaded by Yugoslav Shopping Tourists / by Slobodan Stankovic